Grãos de canola na alimetação de vacas leiteiras : consumo, digestibilidade e eficiência de síntese microbiana - Santos, Wallacy Barbacena Rosa dos (2007)
The experiment aimed to evaluate the effect of canola seed processing (extrusion) and lignosulfonate addition on the parameters: nutrients intake and digestibility and microbial efficiency synthesis. It was used four Holstein cows with average body weight of 538.03±9.98 kg alocated on a latin square design with four periods of 21 days each one. The treatments were: ground canola seed (GCSE), ground and extrused canola seed (GECS), ground canola seed with lignosulfonate (GCSL) and ground and extrused canola seed with lignosulfonate (GECL). It was determinated dry matter (DM), crude protein (CP), ether extract (EE), neutral detergent fiber (NDF) and acid detergent fiber (ADF) intake; DM, CP, organic matter (OM), EE, NDF and ADF total apparent digestibility; DM, OM, CP and EE ruminal digestibility; DM, OM, CP and EE intestinal digestibility. The ruminal bacteria were isolated and analised to determine DM, OM, ash, total nitrogenium and CP. It was also analised parameters that show the microbial synthesis efficiency as: OM rumen apparently degradable OM rumen true degradable and apparent and true microbial synthesis. Nutrients intake did not differ among cows fed with ground canola seed, extrused or not, with or without lignosulfonate. Total apparent digestibility of nutrients was not affected by treatments, except OM wich was increased in ground canola seed. The CP and DM ruminal digestibility decreased with ground and extrused canola seed. However, intestinal digestibility was not affected by treatments. Microbial efficiency synthesis was higher for cows fed with extrused and ground canola seed. In conclusion, the heat process affected the most part of analysed parameters.